How To Collect Cross-Linguistic Data On Valency Online - Gaszewski, Jerzy (Research in Language, 2025)
The paper presents a method of online collection of linguistic data from informants, developed in a cross-linguistic project on verbal valency in the languages of Europe. The method is essentially an online questionnaire. The rules of the creation of its contents as well as specific problems related to data provision and data annotation are discussed in detail. The proposed method ensures the appropriate level of detail needed, enables the collection of a database sizeable enough and secures the comparability of the data.